Inefficient integration during multiple facial processing in pre-morbid and early phases of psychosis. (28th May 2022) - Zhang, TianHong; Yang, YingYu; Xu, LiHua; Tang, XiaoChen; Hu, YeGang; Xiong, Xin; Wei, YanYan; Cui, HuiRu; Tang, YingYing; Liu, HaiChun; Chen, Tao; Liu, Zhi; et al.
Abstract: Objectives: We used eye-tracking to evaluate multiple facial context processing and event-related potential (ERP) to evaluate multiple facial recognition in individuals at clinical high risk (CHR) for psychosis. Methods: In total, 173 subjects (83 CHRs and 90 healthy controls [HCs]) were included and their emotion perception performances were accessed. A total of 40 CHRs and 40 well-matched HCs completed an eye-tracking task where they viewed pictures depicting a person in the foreground, presented as context-free, context-compatible, and context-incompatible. During the two-year follow-up, 26 CHRs developed psychosis, including 17 individuals who developed first-episode schizophrenia (FES). Eighteen well-matched HCs were made to complete the face number detection ERP task with image stimuli of one, two, or three faces. Results: Compared to the HC group, the CHR group showed reduced visual attention to contextual processing when viewing multiple faces. With the increasing complexity of contextual faces, the differences in eye-tracking characteristics also increased. In the ERP task, the N170 amplitude decreased with a higher face number in FES patients, while it increased with a higher face number in HCs. Conclusions: Individuals in the very early phase of psychosis showed facial processing deficits with supporting evidence of different scan paths during context processing and disruption of N170 during multiple facial recognition.